Contextual Role of Woman Board on Sustainability Practice: Evidence from Indonesian University - Fidiana Fidiana (Advanced Research in Economics and Business Strategy Journal)
This research seeks to explore good practices of sustainability in higher education. 30 Indonesian HEIs are participating in UI Green Metric, selected as research objects because they have represented real sustainability actions in higher education. There are 1147 universities in 95 countries in 2024 as participants in UI Green Metric. Content analysis was conducted to identify and present research data. Data sources were obtained from university websites by targeting important documents such as university strategic plans. Artificial intelligence tools like Perplexity supported content searches with sustainability, green, and environmentally friendly keywords. This research found that most HEIs formed SDG centre units at the institutional level as formal evidence of sustainability commitment. Green campus designs with green space, buildings, and behaviour were also developed to implement sustainability actions. In educational activities and curriculum, several HEIs have sustainably packaged their curriculum with several strategies, such as creating new sustainability courses. The development of this sustainability course is supported by the Masudem international program in the form of a consortium of ASEAN countries (6 countries, 3 of which are from Indonesia) and Europe (6 countries).